John H. Towers papers - Towers, John H. (John Henry), 1885-1955.; Norton, Reuben S.; Towers, Pierrette Anne.; Towers, William M.
Correspondence, memoranda, diaries, writings, speeches, reports, aviation logs, biographical material, clippings, blueprints, photographs, and other papers relating chiefly to Towers's career in the U.S. Navy and as vice president of Pan American Airways Corporation. Subjects include his advocacy of naval aviation, his service with the Great White Fleet on its round the world voyage (1907-1909), Curtiss-Wright aircraft, the transatlantic flight of 1919, and American aerial operations in the Pacific during World War II. Includes notebooks compiled by Towers's wife, Pierrette Anne, when gathering information for a biography of Towers. Correspondents include Clementine Churchill and Henry James.
Also includes reminiscences (1900) of William S. Towers concerning his Civil War service with Confederate General Nathan Bedford Forrest, photocopies of a travel journal (1830) kept by Reuben S. Norton while traveling from Massachusetts to New Orleans, La., and Georgia, and a typewritten transcript of Norton's diary (1861-1895) of life in Rome, Ga., kept primarily during the Civil War.
Library of Congress Prints and Photographs Division.
Naval officer and pioneer aviator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation Collection.
Keywords: Forrest, Nathan Bedford, -- 1821-1877.; Churchill, Clementine, -- 1885-1977 -- Correspondence; James, Henry, -- 1843-1916 -- Correspondence; United States. -- Navy -- Aviation; United States. -- Navy -- Cruise, 1907-1909.; United States. -- Navy -- Officers; Pan American Airways Corporation; Aeronautics, Commercial; Aeronautics, Military; Curtiss-Wright aircraft; Naval aviation; Transatlantic flights; Voyages around the world; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Pacific Ocean; Georgia -- Description and travel; Georgia -- History -- Civil War, 1861-1865.; Louisiana -- New Orleans -- Description and travel; Mississippi -- Description and travel; Rome (Ga.) -- History; United States -- History -- Civil War, 1861-1865.; Aviators; Naval officers